Nilai Pendidikan Merdeka Dalam Novel Guru Aini Dan Upaya Peningkatan Mutu Pendidikan Indonesia - Suciartini, Ni Nyoman Ayu; Filisia, Filisia (Jurnal Penjaminan Mutu, 2020)
The government has designed the concept of independent learning to improve the quality of education in the current era. The concept of independent learning is actually not a new concept. The concept of free learning that provides awareness of students and educators to be able to construct their own knowledge and give meaning based on independent learning experiences is closely related to the theory of constructivist learning. In terms of improving the quality of education in Indonesia, many media can be used as a forum or inspiration. One of them, namely literature. The novel Guru Aini by Andrea Hirata is a literary work that deserves to be an inspiration especially to explore the narratives delivered. The formulation of the problem of this research is how is the inspiration for independent learning in this Guru Aini Novel as improving the quality of Indonesian education? The purpose of this study is to describe the values of independent learning in this Guru Aini Novel as improving the quality of Indonesian education. The method used is the analysis of literary sociology and its relation to the theory of constructivist learning. The results of this study indicate that the narratives in the novel "Guru Aini" by Andrea Hirata provide insights related to meaning in the learning process. Knowledge that has to be constructed by itself, is sought by itself with the support and motivation of the teacher as a facilitator as well as a mediator and can help students in solving each problem and bring independence, not depressed, and appreciate every learning process from the inspiration of Aini, Desi, and other figures.